121. Improving Predictive Value of Phase 2a TB Drug Development Models Through PET/CT Imaging (NexGen EBA). (26th November 2018) - Xie, Yingda; Via, Laura; Chen, Ray; Dodd, Lori; Cai, Ying; Paripati, Paveen; Goldfeder, Lisa; Winter, Jill; Arora, Kriti; Wang, Jing; De Jagar, Veronique; Malherbe, Stephanus; et al.
Abstract: Background: Current Phase 2a methods in tuberculosis (TB) drug development are severely limited in capturing a drug candidate's sterilizing activity (ability to prevent TB relapse). We hypothesize that sputum-based measurements of current methods fail to capture drug activity in deep TB lesion compartments, where recalcitrant TB populations are sequestered. In our recent marmoset study, we found complementary 14-day PET/CT delta signatures across different TB lesion compartments that distinguish drugs with long-term sterilizing activity (e.g., rifampin and pyrazinamide) versus drugs with primarily early bactericidal activity (e.g., isoniazid) (Figure 1). We proceeded to evaluate this novel PET/CT Phase 2a approach among TB patients, benchmarked by drugs that are well-characterized clinically and pharmacokinetically. Methods: HIV-negative patients with smear-positive pulmonary tuberculosis from Cape Town, South Africa were enrolled and randomized to receive a single drug [isoniazid (H), rifampin (R), pyrazinamide (Z), moxifloxacin (M)], a 2-drug regimen (HZ, RZ), or a 4-drug regimen (HRZE, MRZE) for 14 days in an inpatient facility. Primary data points were PET/CT scans evaluated at pretreatment baseline and treatment day 14 (and day 28 in the HRZE arm), and daily overnight sputum for early bactericidal activity measurements. Results: From December 2015 to September 2017, 160 participants completed the study, from whom 340 PET/CT scans and 2, 238 overnight sputum samples were collected. PET/CT scans from participants demonstrate diversity of lesion architecture and inter-individual variation in PET/CT changes over 14 days of treatment (Figure 2). A preliminary computational algorithm and first- and second-order PET/CT statistics have been developed for initial segmentation and TB lesion categorization of all study scans. Derivation of radiologic signatures by analysis of 14-day PET/CT changes across each lesion type is ongoing; blinded prediction of each participant's treatment arm based on these signatures is expected by third-quarter 2018. Conclusion: If successful, these signatures may be applied within a 14-day Phase 2a framework to evaluate new TB drug candidates and construct TB drug regimens with complementary lesion pharmacokinetics. Disclosures: All authors: No reported disclosures.